Adults’ food skills and use of gardens are not associated with household food insecurity in Canada - Huisken, Anne (Can J Public Health, 2016)
OBJECTIVES: To determine the extent to which Canadian adults’ food preparation and cooking skills and use of home or community gardens relate to their household food insecurity status; and to compare the food shopping and cooking behaviours of adults in food-secure and food-insecure households. METHODS: Data were drawn from two Rapid Response Modules appended to the Canadian Community Health Survey in 2012 and 201 3. The analytic sample comprised 16,496 respondents 18 years and older. Multivariable logistic regression analyses were conducted to determine the association between food insecurity and adults’ self-rated cooking abilities, food preparation skills score, use of gardens, food shopping behaviours, and cooking behaviours, while adjusting for socio-demographic characteristics. RESULTS: Adults in food-insecure households did not differ significantly from others with respect to their food preparation skills or cooking ability, and neither variable predicted the odds of household food insecurity when socio-demographic characteristics were taken into account. Adults in food-insecure households were less likely to use a garden for food, but gardening was unrelated to the odds of food insecurity. Shopping with a budget was more common among adults in food-insecure households, but no other differences in food shopping behaviours were observed after adjustment for socio-demographic characteristics. Adults in food-insecure households were as likely as others to adjust recipes to make them healthier, but they had higher odds of adjusting recipes to reduce their fat content. CONCLUSION: Our findings suggest that household food insecurity in Canada is not a problem of insufficient food skills.